Evolución geoquímica del magmatismo cretácico superior-paleoceno inferior en los Andes Centrales (34-36°S) - Iannelli, Sofía (2019)
Geochemical evolution of Late Cretaceous-early Paleocene magmatism in the Southern Central Andes (34-36°S). Late Cretaceous-early Paleocene magmatism shows a disperse distribution and contrasting geochemical signature along the Andean margin. In particular, Los Ángeles Unit (67 Ma) presents a tholeiitic signature with decreasing slab-fluids influence and partial melting degrees and a general enrichment in REE elements from the base to the top of the sequence. An isotopically enriched to depleted mantle source is also registered during the evolution of this magmatic unit.